Pendampingan Pencegahan Covid-19 Melalui Program Donasi Wastafel Darurat di Kelurahan Kapas Kec. Sukomoro Kab. Nganjuk - Miftakhul Kholifah; Rohmad (LP3M IAIFA Kediri, 2020)
Now social community environment sometimes not remember to wich advocates adhering to health protocol in pandemic. Based on that context community assistance program will be implemented and directed for always keep the health and healty and clean lifestyle. Always wash yours hads whith soap and adhering to protocol in order to prevent more transmission. In this assistance program and there is donation of place for washing hands and soap for washing hands. This assistance community considered quite susscessful because there is public awareness of the importance of pereventing the spread of the covid 19 virus wich are widely spread in this country, keep your healty with always keep your clean style. In this accompaniment also raises excellent cooperation and communication from the community and researchers as well Kapas village Nganjuk as the active role of the community in the success program . The number of sink donation were given to prevent the spread of covid 19 were 12 hand washing places. After the sink donation given the community is very participating and implementing protocol to always wash hands to prevent the spread of the covid 19 virus more. The success of this program has also become an indifference to getting used to a clean and healty life.